THE INFLUENCE OF SERVICE QUALITY AND EXPERIENTIAL MARKETING ON CUSTOMER LOYALTY: CUSTOMER SATISFACTION AS MEDIATION - Wulandari, Shofia; Rahayu, Yayuk Sri (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This study aims to determine the effect of service quality and experiential marketing on customer satisfaction and loyalty.  The type of research is quantitative and conducted at Bank Muamalat KC Malang with 100 customers as respondents, using purposive sampling technique. data analysis in this study using PLS-SEM. The results shows that service quality and experiential marketing has a significant positive impact on customer satisfaction, service quality and experiential marketing has a significant positive impact on customer loyalty, and customer satisfaction has a significant impact on customer loyalty.  Customer satisfaction role as a mediator between service quality and experiential marketing to customer loyalty. The implication of this research in theory is to strengthen the existing theory of customer satisfaction and loyalty and practically is that Muamalat Bank KC Malang should pay more attention to providing aspects of service quality and experiential marketing that can increase customer satisfaction and loyalty.